1969
DOI: 10.1139/m69-087
|View full text |Cite
|
Sign up to set email alerts
|

A broad-spectrum antibiotic produced by a species of Cryptosporiopsis

Abstract: A growth inhibitor with the molecular formula C10H10O4Cl2 was isolated from a medium which had supported growth of a species of Cryptosporiopsis, an imperfect fungus. The compound was named cryptosporiopsin and was characterized on the basis of its physical and chemical properties. Cryptosporiopsin was active in vitro against many wood-rotting basidiomycetes as well as some phycomycetes, ascomycetes, and deuteromycetes. It was more effective than Dithane M-22 or nystatin against the in vitro spore germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…infrared (CHCl3): 3,345 (OH), 1,671 cm-1 (C = 0); EIMS: m/z 138 (M -H20; 1.0% of base peak), 121 (3), 112 (15), 110 (19), 97 (12), 96 (16), 82 (18), 81 (26), 71 (33), 69 (28), 55 (52), 53 (100), 43 (48), 41 (47), 39 (94), 31 (50); CIMS: mlz 157 (M + H; base peak); 1H NMR (acetone-d6): signals at 6.70 (m, 1H), 4.84 (broad s, 1H, D20 exchangeable), 4.65 (m, 1H), 4.25 (broad d, J = 16 Hz, 1H), 4.15 (broad d, J = 16 Hz, 1H), 4.09 (broad s, 1H, D20 exchangeable), 3.77 (ddd, J = 3.7, 2.6, 1.4 Hz, 1H), and 3.40 ppm (dd, J = 3.7, 1.2 Hz, 1H); 13C NMR (acetone-d6): signals at 194.3 (s), 139.2 (d), 137.0 (s), 63.3 (d), 59.0 (t), 58.8 (d), and 54.1 ppm (d); HRCIMS: observed; mlz 157.0492 (M + H). Calculated for C7H804 + H: 157.0500.…”
Section: Resultsmentioning
confidence: 99%
“…infrared (CHCl3): 3,345 (OH), 1,671 cm-1 (C = 0); EIMS: m/z 138 (M -H20; 1.0% of base peak), 121 (3), 112 (15), 110 (19), 97 (12), 96 (16), 82 (18), 81 (26), 71 (33), 69 (28), 55 (52), 53 (100), 43 (48), 41 (47), 39 (94), 31 (50); CIMS: mlz 157 (M + H; base peak); 1H NMR (acetone-d6): signals at 6.70 (m, 1H), 4.84 (broad s, 1H, D20 exchangeable), 4.65 (m, 1H), 4.25 (broad d, J = 16 Hz, 1H), 4.15 (broad d, J = 16 Hz, 1H), 4.09 (broad s, 1H, D20 exchangeable), 3.77 (ddd, J = 3.7, 2.6, 1.4 Hz, 1H), and 3.40 ppm (dd, J = 3.7, 1.2 Hz, 1H); 13C NMR (acetone-d6): signals at 194.3 (s), 139.2 (d), 137.0 (s), 63.3 (d), 59.0 (t), 58.8 (d), and 54.1 ppm (d); HRCIMS: observed; mlz 157.0492 (M + H). Calculated for C7H804 + H: 157.0500.…”
Section: Resultsmentioning
confidence: 99%
“…The paper disc assay method described by Stilwell et al (1969) was used to obtain the antimicrobial spectrum of phacidin. The paper discs were prepared by dissolving 25.0 mg crystalline phacidin in 25.0 ml 95% ethanol and Can.…”
Section: Assay Of Pl~acidirlmentioning
confidence: 99%
“…Control antibiotics were not run with this series, but the action of penicillin and other commercial antibiotics against these bacteria is well known, under identical conditions (Stilwell et al 1969).…”
Section: Antimicrobial Spectrum Of Phacidinmentioning
confidence: 99%
“…The structure of (+)-crytosporiopsin (16) was confirmed by x-ray crystallography (McGahren et al 1969) and has the S configuration at positions 1 and 5. It is not surprising that (+)-crytosporiopsin (16) was isolated from a P. sporulosa endophyte since one of the original reports of this metabolite was from its anamorphic state, Cryptosporiopsis, isolated from decaying Betula alleghaniensis (yellow birch; Stillwell et al 1969;. Interestingly, the P. sporulosa endophyte studied here was collected from as an endophyte of red spruce in a yellow birch and red maple stand.…”
Section: Metabolites Of Pezicula Sporulosa (Nb382-3d Daom 250862)mentioning
confidence: 93%
“…In a study of Pezicula endophytes isolated from asymptomatic deciduous and coniferous tree branches in Northern Germany, (+)-crytosporiopsin (16) was characterized from six of the eighty five strains studied (Schulz et al 1995). This chlorinated natural product possesses antifungal activity against several other wood rot fungi and is antibiotic (Stillwell et al 1969). The authors suggested this biologically active metabolite could be applied to prevent the deterioration of forest products or control diseases of agriculture and forests.…”
Section: Metabolites Of Pezicula Sporulosa (Nb382-3d Daom 250862)mentioning
confidence: 99%